Metabolism and Regulatory Functions of O-Acetylserine, S-Adenosylmethionine, Homocysteine, and Serine in Plant Development and Environmental Responses - Watanabe, Mutsumi; Chiba, Yukako; Hirai, Masami Yokota (Frontiers in Plant Science, 2021)
The metabolism of an organism is closely related to both its internal and external environments. Metabolites can act as signal molecules that regulate the functions of genes and proteins, reflecting the status of these environments. This review discusses the metabolism and regulatory functions of O-acetylserine (OAS), S-adenosylmethionine (AdoMet), homocysteine (Hcy), and serine (Ser), which are key metabolites related to sulfur (S)-containing amino acids in plant metabolic networks, in comparison to microbial and animal metabolism. Plants are photosynthetic auxotrophs that have evolved a specific metabolic network different from those in other living organisms. Although amino acids are the building blocks of proteins and common metabolites in all living organisms, their metabolism and regulation in plants have specific features that differ from those in animals and bacteria. In plants, cysteine (Cys), an S-containing amino acid, is synthesized from sulfide and OAS derived from Ser. Methionine (Met), another S-containing amino acid, is also closely related to Ser metabolism because of its thiomethyl moiety. Its S atom is derived from Cys and its methyl group from folates, which are involved in one-carbon metabolism with Ser. One-carbon metabolism is also involved in the biosynthesis of AdoMet, which serves as a methyl donor in the methylation reactions of various biomolecules. Ser is synthesized in three pathways: the phosphorylated pathway found in all organisms and the glycolate and the glycerate pathways, which are specific to plants. Ser metabolism is not only important in Ser supply but also involved in many other functions. Among the metabolites in this network, OAS is known to function as a signal molecule to regulate the expression of OAS gene clusters in response to environmental factors. AdoMet regulates amino acid metabolism at enzymatic and translational levels and regulates gene expression as methyl donor in the DNA and histone methylation or after conversion into bioactive molecules such as polyamine and ethylene. Hcy is involved in Met–AdoMet metabolism and can regulate Ser biosynthesis at an enzymatic level. Ser metabolism is involved in development and stress responses. This review aims to summarize the metabolism and regulatory functions of OAS, AdoMet, Hcy, and Ser and compare the available knowledge for plants with that for animals and bacteria and propose a future perspective on plant research.